PERBANDINGAN HASIL BELAJAR BIOLOGI MENGGUNAKAN STRATEGI EVERYONE IS A TEACHER HERE DENGAN LEARNING STARTS WITH A QUESTION SISWA KELAS VII SMP NEGERI 2 KOTO BESAR KABUPATEN DHARMASRAYA - Maria, Siska - (STKIP PGRI Sumbar, 2014)
The results of studying biology class VII Junior High School 2 Koto Besar is still low, due to the lack of participation of students participated in the group, less responsible for the tasks assigned by the teacher. This study aimed to determine differences in the biology of learning outcomes using ETH strategy and LSQ VII grade students of SMP Negeri 2 Koto Besar. This study was conducted May 12 to June 7, 2014 Junior High School VII grade 2 Koto Besar. The study design was a randomized experimental design and Only Control Group Design. The study population was a VII grade students of SMP Negeri 2 Koto Besar and sample classes VII6 VII1 and graders. Analysis using t test. The results of the data analysis that the value t_hitung = 2.18 while t_table 1.67, mean t count> t table. In conclusion there are differences in the biology of learning outcomes using strategies Everyone Is A Teacher Here with Learning Starts With A Question VII grade students of SMP Negeri 2 Koto Besar Dharmasraya District.